The Impact of Tax Audit and Corruption Perception on Tax Evasion - Ferry Irawan; Adam Siaga Utama (International Journal of Business and Society, 2021)
This study is aimed to determine the impact of tax audit intensity and perception of corruption on tax evasion activities. Some research that explains the impact of tax audit on tax evasion tends to give a varied result one and another. It is reasonable to assume that there is another factor that simultaneously influences tax evasion. Tax audit and perception of corruption were chosen because of their relevance and intertwine relation in tax authorities function and program, namely tax enforcement and the eradication of corruption. This research is also in line with the challenges faced by many countries in increasing tax compliance. We conduct a panel data regression method with a fixed effect model. We found that tax audit proved insignificant to tax evasion, and perception of corruption positively significant to tax evasion. We conclude that corruption significantly increases tax evasion and undermine the benefit of tax audit